Analisis Kemampuan Mengonstruksi Bukti Matematis dalam Menyelesaikan Soal Pembuktian Geometri Transformasi - Silwana, Amalia (Universitas Islam Jember, 2023)
This research aims to describe the undergraduate students’ ability to construct mathematical proofs with high, medium, and low mathematical abilities in solving Transformation Geometry proof problems. This research is descriptive qualitative research with three undergraduate students of the Mathematics Education department as research subjects: one high-ability undergraduate student, one medium-ability undergraduate student, and one low-ability undergraduate student. The research results show that high-ability undergraduate students can fulfill all the indicators of construct mathematical proofs ability, medium-ability undergraduate students are unable to show warrant as a link to the premises and conclusions of statements so they cannot continue the proof correctly and fulfill the indicators of construct mathematical proofs ability, while low-ability undergraduate students are unable to state the relation between premises and the relation between premises and conclusions of statements so they cannot continue the proof correctly and fulfill the indicators of construct mathematical proofs ability Keywords: construct mathematical proofs, transformation geometry